The science of nutrition - Needham, Jennie June (My University, 1899)
Introduction: This science deals with the underlying principles of food substances, their value and use. It may fall under two man heads, the one having for its field the investigation of the food supply and the habits of the people, the other dealing with the relation of physiology and chemistry to food and nutrition. At the beginning of this century, various philanthropic efforts were made in France and Germany to better the condition of the poor, and these investigations show that this is a broad field for work, and that the science of nutrition embraces not only a thoro understanding of physiology and chemistry, but also of sanitation, hygiene and dietetics. Thus we find that altho noon has formulated a definition for this subject, nevertheless, it is a broad science and one upon which many other sciences are dependent.
Citation: Needham, Jennie June. The science of nutrition. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Relation of Physiology and Chemistry; Food Principles; Relation of nutrition to Civilization; Theses; Manuscripts (documents)